2021
DOI: 10.1002/ijc.33803
|View full text |Cite
|
Sign up to set email alerts
|

How do age and social environment affect the dynamics of death hazard and survival in patients with breast or gynecological cancer in France?

Abstract: Several studies have investigated the association between net survival (NS) and social inequalities in people with cancer, highlighting a varying influence of deprivation depending on the type of cancer studied. However, few of these studies have accounted for the effect of social inequalities over the follow‐up period, and/or according to the age of the patients. Thus, using recent and more relevant statistical models, we investigated the effect of social environment on NS in women with breast or gynecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…These results are in line with previous research from other countries. In a French study using population-based data, Poiseuil et al showed that socioeconomic factors were associated with net survival among breast and gynaecological cancer patients [ 31 ]. Another study from France showed that a number of barriers to cervical screening attendance were associated with low socioeconomic status [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with previous research from other countries. In a French study using population-based data, Poiseuil et al showed that socioeconomic factors were associated with net survival among breast and gynaecological cancer patients [ 31 ]. Another study from France showed that a number of barriers to cervical screening attendance were associated with low socioeconomic status [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have, however, focused on differences in mortality rates [ 31 , 34 ]. Sassenou et al [ 35 ] concluded that obese women were less likely to undergo cervical cancer screening and at the same time more often lived in areas with low socioeconomic status, thus being particularly vulnerable.…”
Section: Discussionmentioning
confidence: 99%